Online clinic claim system / Tengku Aliff Faisal Tengku Ahmad - Tengku Ahmad, Tengku Aliff Faisal (2007)
Developments in web technology have made most of our daily life applications more easy and manageable. The Internet has become a common medium of communication and is found in various places such as offices, homes, and hospitals. The services obtained from the Internet can reduce the gap of communication between any two users, e.g., the users and the health centers. Besides a host of services provided via this scenario, the user can access significant health information. The concept of the web-based health center is not new and there is always some room for modifications, improvements, and adoption of new technologies. The common feature shared among most of these healthcare providers is to establish secure, confidential, and retrievable electronic transactions to the users. It is fundamental in such situations to strengthen the physicianpatient relationship by facilitating communication and simplifying transactions to achieve optimum health services.The main purpose of this research is to assist clinical personnel such medical staff and medical consultant to run clinic daily activities through the computer-based clinic system and the used of the electronic data. This research focused on the development of web-based application for the clinic system application which can give long term benefits to them. This application is developed using the open source software such as Apache Web Server, MySQL Database, phpMyAdmin Database Administrator plus with PHP programming language.